2014
DOI: 10.1016/j.febslet.2013.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an arylalkylamine N‐acyltransferase from Drosophila melanogaster that catalyzes the formation of long‐chain N‐acylserotonins

Abstract: Arylalkylamine N-acyltransferase-like 22 (AANATL2) from Drosophila melanogaster was expressed and shown to catalyze the formation of long-chain N-acylserotonins and N-acydopamines. Subsequent identification of endogenous amounts of N-acylserotonins and colocalization of these fatty acid amides and AANATL2 transcripts gives supporting evidence that AANATL2 has a role in the biosynthetic formation of these important cell signalling lipids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 26 publications
(39 reference statements)
9
64
0
Order By: Relevance
“…Another consideration regarding the presence of long-chain fatty acids in Drosophila is potential variations in the cellular levels of these compounds in different tissues [Table 2 and ref. 14], at different stages of development [24,32,33], and due to differences in their diet [29,31,34], further complicating reports of these trace metabolites. Similar conclusions regarding presence of ≥C 20 fatty acids and their metabolites were reached by Vrablik and Watts in a recent review [35].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another consideration regarding the presence of long-chain fatty acids in Drosophila is potential variations in the cellular levels of these compounds in different tissues [Table 2 and ref. 14], at different stages of development [24,32,33], and due to differences in their diet [29,31,34], further complicating reports of these trace metabolites. Similar conclusions regarding presence of ≥C 20 fatty acids and their metabolites were reached by Vrablik and Watts in a recent review [35].…”
Section: Resultsmentioning
confidence: 99%
“…Our demonstration that flies fed a diet supplemented with [1- 13 C]-palmitic acid led to the formation of 13 C- N -palmitoyldopamine, 13 C- N -palmitoylglycine, and 13 C-palmitamide is consistent with, but does not prove, that palmitoyl-CoA in a central palmitoyl donor in the biosynthesis of the different classes of palmitoylated fatty acid amides. We have recently identified and characterized an enzyme from D. melanogaster that catalyzes the formation of long-chain N -acylarylalkylamides, notably the N -acylserotonins and the N -acyldopamines, from the corresponding long-chain acyl-CoA thioesters and arylakylamine: acyl-CoA + serotonin (or dopamine) → N -acylserotonin (or N -acyldopamine) + CoA [14]. Importantly, we also found that the expression pattern of this enzyme in D. melanogaster co-localized to the tissues containing measurable levels of the endogenous long-chain N -acylserotonins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increases in N-acyldopamine levels were unexpected, but could be due to an increase in acyl-CoAs available for conjugation to dopamine by an unidentified arylalkylamine N-acyltransferase-like (AANATL) enzyme. In Drosophila, AANATL2 catalyzes the formation of long-chain N-acyldopamines in vitro (35,36) and we propose that a mammalian AANATL2 ortholog could be responsible for N-acyldopamine formation in the N 18 TG 2 cells.…”
Section: Cells Express Glyatl3 Transcriptsmentioning
confidence: 86%
“…14 We have proposed that one route for the biosynthesis of the fatty acid amides involves the reaction of an amine with a fatty acyl-CoA in a reaction catalyzed by an N- acyltransferase: R-CO-S-CoA + H 2 N-R′ → R-CO-NH-R′ + CoA-SH. Drosophila melanogaster is an excellent model system for the study of fatty acid amide metabolism because these insects (a) produce fatty acid amides, 24 (b) are inexpensive to grow and maintain, (c) possess a genome that has been sequenced, and (d) can be manipulated genetically with relative ease. Intriguingly, we and others have identified the genes of seven putative N -acyltransferases in D. melanogaster by “genome mining” using the DNA sequences of known N- acetyltransferases.…”
mentioning
confidence: 99%